Profilaktična cepiva na osnovi informacijske rna proti nalezljivim boleznim - Vencelj, Ana (Farmacevtski vestnik, 2021)
Messenger RNA (mRNA) vaccines are an extremely promising vaccine platform, as they allow for immediate response to new pathogen threats. mRNA vaccines are based on introducing genetic information for one or more antigens of a pathogen directly into cells of a vaccinated individual. The transfected cells use this genetic information to transiently express the encoded protein antigen and display it on the cell surface in the form of antigenic peptides bound to major histocompatibility complex, thereby activating T lymphocytes. If the encoded intact antigen is directed to the cell surface or the extracellular space, robust humoral response is also observed. In the last decade, important progress has been made in the areas of enzymatic mRNA synthesis, understanding immunomodulatory properties of exogenous mRNA as well as materials for mRNA delivery, and optimizing transfection and in vivo translation efficiency, leading to approval of first mRNA-based vaccines in the European Union and United States. here, we review the mechanisms of actions, production technologies and current clinical experience with prophylactic mRNA vaccines against infectious diseases.
Keywords: Cepiva; cepivo informacijske RNA; Infekcijske bolezni; Klinične raziskave; mehanizem delovanja; mRNA